Dacotu TikTok Account To Master English: EFL Students' Perspective: Akun TikTok Dacotu Untuk Menguasai Bahasa Inggris: Perspektif Siswa Bahasa Inggris - -, Kris Inayah Hasnia Aziz; Maulida Amanda Putri; Eliasanti Agustina (Universitas Islam Negeri (UIN) Mataram, 2024)
TikTok is an application that may be utilized as a learning medium as long as it is used appropriately. In this study, TikTok can be an effective tool for EFL students to master English skills. One of the TikTok recommendation for English learning is Dacotu. Therefore, the study aims to investigate advantages and disadvantages Dacotu TikTok account as learning medium to master English language through students' perspective. This research applied qualitative descriptive method. To collect the data, the researcher used questionnaire to consider EFL students’ perspectives of English Language Education in English Language Education Department at Universitas PGRI Adi Buana Surabaya. The finding of research revealed Dacotu TikTok account can be a supporting to master English for EFL students. Dacotu TikTok account have positive and negative impacts for EFL students during English learning. In addition, the researcher also suggests English influencer in TikTok to perform English learning that can encourage EFL students learn English as well.